2021
DOI: 10.1007/s40744-021-00342-8
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α Blockers Showed Prophylactic Effects in Preventing COVID-19 in Patients with Rheumatoid Arthritis and Seronegative Spondyloarthropathies: A Case–Control Study

Abstract: Introduction:The interaction between angiotensin-converting enzyme 2 (ACE2) and SARS-CoV-2 is a crucial factor in the viral infections leading to the release of inflammatory proteins, such as TNF-a. Thus, it is hypothesized that TNF-a blockers can prevent either COVID-19 incidence or its serious symptoms. TNF-a blockers are prescribed to treat various autoimmune disorders, including rheumatoid arthritis (RA) and seronegative spondyloarthropathies (SpA). Therefore, the objective of this work was to examine this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…And the highest percentage of impact on the prevention of COVID-19 was related to adalimumab (96.8%). Their result could also confirm that TNF-α inhibitors may mitigate or ameliorate the COVID-19 disease course (90). Overall, patients with COVID-19 using anti-TNF therapy do not fare worse than those treated with other drugs.…”
Section: Potential Of Tnf-α Inhibitors In Covid-19mentioning
confidence: 85%
“…And the highest percentage of impact on the prevention of COVID-19 was related to adalimumab (96.8%). Their result could also confirm that TNF-α inhibitors may mitigate or ameliorate the COVID-19 disease course (90). Overall, patients with COVID-19 using anti-TNF therapy do not fare worse than those treated with other drugs.…”
Section: Potential Of Tnf-α Inhibitors In Covid-19mentioning
confidence: 85%
“…Finally, Kridin et al recently analyzed outcomes of COVID-19 in patients with psoriasis treated with anti-TNF biologics and found that TNF blockade significantly decreased the risk of COVID-19 associated hospitalization. The authors did not see reduction in mortality, but mortality events were very low in this study [ 45 ]. These observations also suggest that immunosuppressive properties of TNF blockers do not exacerbate viral disease due to a weakened clearance of the pathogen.…”
Section: Blocking Tnf Upstream Of Tnf Receptorsmentioning
confidence: 70%
“…Later, a meta-analysis of more than 6000 cases revealed that TNF inhibitors administered to patients with immune-mediated inflammatory diseases alone were better protectors from severe COVID-19 associated hospitalizations and deaths than azathioprine/6-mercaptopurine or methotrexate [ 44 ]. Another study reported that TNF blockers administered to patients with rheumatoid arthritis and spondyloarthropathies significantly (by > 80%) reduced the risk of COVID-19 infection [ 45 ].…”
Section: Blocking Tnf Upstream Of Tnf Receptorsmentioning
confidence: 99%
“…The importance of IL-10/IFN-γ producing T cells have also been highlighted by two recent works: such a functional T cell profile was demonstrated to be defective in severe COVID-19 (30), while the presence of IL-10 producing Spike-specific T cells is characteristic of individuals with hybrid SARS-CoV-2 immunity (29) who demonstrate a robust immunity from re-infection (38,39). Of note, the demonstration that mRNA vaccination in IBD patients undergoing TNF inhibition results in the induction of T cells with an IFN-γ/IL-2/IL-10 secretion profile suggests that similar functional profiles might likewise be induced in virus-specific T cells after SARS-CoV-2 infection, explaining the clinical evidence that SARS-CoV-2 infection in different patients undergoing TNFi treatment is generally mild (40)(41)(42). In our own study, 6 patients who eventually developed COVID-19 all had a mild disease course and did not require hospitalization; 4 of whom were on TNFi.…”
Section: Discussionmentioning
confidence: 99%